Addenda to the fauna of Cicadina (Hemiptera) of Bulgaria - Emeljanov, Alexandr F. (Acta entomologica slovenica (Ljubljana), 2002)
New data on the distribution of 50 species of Cicadina in Bulgaria, including 44 species first recorded, are presented. Arboridia stranjensis Bayryamova, 1987 is placed in synonymy with fagocyba carri (Edwards, 1914)
Keywords: Bolgarija; Bulgaria; favna; Hemiptera; škržati